PENGHANCURAN WARISAN BUDAYA DI TIMBUKTU OLEH ANSAR DINE DI TAHUN 2012: PELANGGARAN TERHADAP KONVENSI DEN HAAG 1954? DESTRUCTION OF CULTURAL HERITAGE IN TIMBUKTU BY ANSAR DINE IN 2012: A VIOLATION OF THE 1954 HAGUE CONVENTION? - Pashya, Habib; Faradila, Muslihah; Nurfitriyani, Resti; Istiqomatunnisa (Fakultas Hukum Universitas Trisakti, 2023)
The armed conflict in Mali since 2012 has had a significant impact on the destruction of various cultural sites, particularly in Timbuktu. The research method used in this research is a literature study by reviewing various relevant literatures on the case study, while using a normative-juridical approach through analysis of the articles of the Hague Convention and international judicial decisions through the articles contained in the Rome Statute. This is because this conflict has resulted in significant violations of the 1954 Hague Convention, which regulates the Protection of Cultural Property in the Event of Armed Conflict as stated in Article 2 regarding the importance of protecting cultural property in conflict areas. Moreover, there have been violations of the Rome Statute governing the jurisdiction of the International Criminal Court (ICC). In addition, this conflict has violated the principles of distinction and precaution as it has resulted in the destruction of civilian objects such as places of worship categorized as cultural heritage. The purpose of this study is to highlight the importance of implementing international law in protecting the cultural heritage owned by every nation. Furthermore, this research emphasizes the importance of stronger international cooperation to protect cultural heritage, especially in areas prone to armed conflict. It also emphasizes the importance of taking firm action against violators of international humanitarian law such as the ICC trial of Al-Mahdi from Ansar Dine for the destruction of cultural heritage in Timbuktu.